Greater syntactic impairments in native language in bilingual Parkinsonian patients. Issue 12 (16th November 2004) - Zanini, S; Tavano, A; Vorano, L; Schiavo, F; Gigli, G L; Aglioti, S M; Fabbro, F
Abstract : Objective: To investigate the presence of syntactic impairments in native language in Parkinson's disease. Methods: Twelve bilingual patients, with Friulian as their first language (L1) and Italian as their second (L2), with Parkinson's disease and 12 normal controls matched for age, sex, and years of schooling, were studied on three syntactic tasks. Results: Patients with Parkinson's disease showed a greater impairment of L1 than L2. Conclusions: These findings provide evidence of greater basal ganglia involvement in the acquisition and further processing of grammar in L1 v L2 possibly due to a major involvement of procedural memory in representing L1 grammar.